PENINGKATAN HASIL BELAJAR IPA MELALUI IMPLEMENTASI MODEL KOOPERATIF TEKNIK PICTURE AND PICTURE - ., mahdi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
The aim of this research is to improve the learning outcomes of science subjects in human and animal organs through the use of the Picture and Picture Technique Cooperative Learning Model in class V of the Julok Cut Elementary School in the second semester of the 2016-2017 academic year. The benefits of this research are to add new references and theories in the field of education, especially the implementation of Classroom Action Research by applying various models or learning methods so as to improve student learning outcomes. To achieve this, the steps that need to be implemented are using the Picture and Picture Technique Cooperative Learning Model. Data analysis method used in this study uses descriptive analysis whose data is sourced from formative tests and classroom observations. This research was conducted in 2 cycles, each cycle consisting of two meetings. Indicators of success in this study are expected to increase students' mastery learning which reached 85% classically. The results showed, in the first cycle the average value of students amounted to 64 and mastery learning reached 44%. These results indicate an improvement from the initial conditions with an average score of only 54.8 and a new learning completeness of 28%. While in cycle II the average value of students was 79.2 and mastery learning reached 92%. The conclusion of this study is the use of the Picture and Picture Technique Cooperative Learning Model in natural science learning materials of human and animal organs can positively influence the improvement of student learning outcomes in the second semester of the second semester of SD Negeri Julok Cut, Julok District, East Aceh Regency.